Effective removal and selective capture of copper from salty solution in flow electrode capacitive deionization. Issue 2 (2nd August 2019) - Zhang, Xudong; Yang, Fan; Ma, Junjun; Liang, Peng
Abstract : The application of flow-electrode capacitive deionization might provide an alternative for water reclamation and selective recovery of copper. Abstract : Heavy metal removal and recovery from industrial wastewaters have aroused great concern. However, selective concentration of these target ions remains a big challenge given the high concentration of interfering ions like Na + . In this study, treatment of salty influents containing copper ions was carried out by flow-electrode capacitive deionization (FCDI) for the removal and recovery of copper. A variety of operation conditions were investigated including the operation mode of the flow electrode, applied voltage, initial pH of the flow electrode and long-term operation. Results showed that separation was achieved in the electrode chamber, since Cu 2+ was preferentially deposited or adsorbed on the carbon particles while Na + was mostly distributed in the electrolyte. This phenomenon was more evident in a short-circuited closed cycle (SCC) mode due to strong Na + desorption. The removal efficiency of Cu 2+ escalated consistently with the increase of applied voltage, and the removed Cu 2+ remained in the carbon particles. The formation of Cu species could be regulated by pH adjustment, and X-ray photoelectron spectroscopy (XPS) analysis confirmed that the low initial pH of the flow electrode contributed to the production of Cu 0 . The Cu 2+ removal performance retained ∼94% of the initial value while for Na + only ∼90% was retained after 24-hour operation, which was related to the co-ion leakage phenomenon; the maximum loading content reached ∼5 mg Cu per g AC.